Effect of CPAP therapy on kidney function in patients with obstructive sleep apnoea and chronic kidney disease: a protocol for a randomised controlled clinical trial. Issue 3 (23rd March 2019) - Rimke, Alex N; Ahmed, Sofia B; Turin, Tanvir C; Pendharkar, Sachin R; Raneri, Jill K; Lynch, Emma J; Hanly, Patrick J
Abstract : Introduction: Obstructive sleep apnoea (OSA) is common in patients with chronic kidney disease (CKD) and may contribute to the progression of kidney disease either through direct effects of hypoxia on the kidney or indirectly through hypoxaemia-induced oxidative stress, endothelial dysfunction, inflammation, activation of the renin–angiotensin and sympathetic nervous systems, and hypertension. Treatment of OSA with continuous positive airway pressure (CPAP) improves many of these physiological abnormalities in patients with normal renal function, though to date there are no trials evaluating the effect of OSA treatment on kidney function in patients with CKD. The purpose of this study is to test the feasibility and efficacy of CPAP therapy in CKD patients with OSA. Methods and analysis: The study is a randomised, controlled, non-blinded, parallel clinical trial in which patients with established CKD are screened for OSA. Patients with OSA are randomised to either conventional medical therapy (control group) or medical therapy and CPAP (CPAP group) and followed for 1 year. The primary outcome is the change in estimated glomerular filtration rate. Secondary outcomes are the change in the urinary albumin/creatinine ratio, the Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index and Kidney Disease Quality of Life questionnaire. Ethics and dissemination: Ethics approval has been obtained from the Conjoint Health Research Ethics Board (ID: REB15-0055). Results from this study will be disseminated through presentations at scientific conferences and publication in peer-reviewed journals. Trial registration number: NCT02420184; Pre-results.